Peningkatan Kinerja Guru melalui Supervisi Klinis di SD Negeri 2 Sakra Tahun Pelajaran 2022/2023 - Jamaluddin, Jamaluddin (Lembaga Yasin AlSys, 2022)
The research conducted is a school action research which raises questions about how teachers can use existing learning media in the learning process in the classroom with the intention of increasing the quality of learning conducted in class and the evaluation is carried out through supervising activities of the principal in class when learning. This school action research activity was carried out at SDN 2 Sakra for 3 months, from October to December 2022 by going through cycle stages. The purpose of this school action research is to find out to what extent the supervision carried out by the school principal followed by the provision of guidance/treatment of target teachers can improve the teacher's ability to apply learning models in class. In school action research this was carried out in 2 cycles, the results of the actions taken proved to be able to improve teacher abilities by achieving ideal standards. In the first cycle of improving the ability of teachers after conducting class supervision after coaching on the use of new learning media reached around 33.33% in cycle II it could increase to 100%. The average score obtained after class supervision in cycle I was 63.30 and increased in cycle II to 83.33, meaning that there was an increase of 20.03 and the level of completeness as a group/classical in cycle I reached 33.33% and in cycle II increased to 100%. The results of this school action research show that school principal coaching can improve teachers' ability to use instructional media in the learning process.